The Role Of Microcredit In Poverty Alleviation In Malaysia - The Case Of The Amanah Ikhtiar Malaysia AIM - Omar, Mohamed Zaini
The emergence of an alternative development model via the Grameen Bank microcredit concept had showcased to the world of how the poor rural households can uplift themselves out of poverty effectively. The Grameen Bank was so successful that it has become the prominent development model, being widely replicated throughout the world and its founder, Professor Muhammad Yunus was the recipient of the 2006 Nobel Laureate for Economic. In 1987 this model was also being implemented in Malaysia by the non-governmental organization and thus was born the Malaysian version of the Grameen microcredit scheme known as the Amanah Ikhtiar Malaysia or AIM.